2022
DOI: 10.1101/2022.05.10.491413
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Epigenetic variation impacts ancestry-associated differences in the transcriptional response to influenza infection

Abstract: SummaryHumans display remarkable inter-individual variation in immune response when exposed to identical immune challenges. Yet, our understanding of the genetic and epigenetic factors contributing to such variation remains limited. Here we carried out in-depth genetic, epigenetic, and transcriptional profiling on primary macrophages derived from a panel of European and African-ancestry individuals before and after infection with influenza A virus (IAV). We show that baseline epigenetic profiles are strongly p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(40 citation statements)
references
References 131 publications
(184 reference statements)
0
39
0
Order By: Relevance
“…Epigenetic mechanisms have been shown to play a central role in the regulation of immune responses to bacterial and viral pathogens. [79][80][81][82][83][84][85][86][87][88][89] Thus, it is likely that variation in epigenetic profiles across individuals and populations considerably contributes to population variation in innate immune responses and susceptibility to disease. The field of population epigenomics has primarily concentrated on the differences in DNA methylation levels among individuals.…”
Section: P Opul Ati On Variati On In the Epi G Enomementioning
confidence: 99%
See 4 more Smart Citations
“…Epigenetic mechanisms have been shown to play a central role in the regulation of immune responses to bacterial and viral pathogens. [79][80][81][82][83][84][85][86][87][88][89] Thus, it is likely that variation in epigenetic profiles across individuals and populations considerably contributes to population variation in innate immune responses and susceptibility to disease. The field of population epigenomics has primarily concentrated on the differences in DNA methylation levels among individuals.…”
Section: P Opul Ati On Variati On In the Epi G Enomementioning
confidence: 99%
“…Recently, however, the scope has expanded to include a wider range of epigenetic modifications and their complex interactions with gene regulation. [89][90][91][92] For example, Aracena et al performed an in-depth genetic, epigenetic, and transcriptional profiling of primary macrophages derived from European-and African-ancestry individuals before and after IAV infection. 89 These data revealed that baseline epigenetic profiles are strongly predictive of the transcriptional response to IAV across individuals, supporting the concept that changes in gene expression in response to IAV infection are, in part, influenced by the pre-existing epigenetic states of an individual's cells.…”
Section: P Opul Ati On Variati On In the Epi G Enomementioning
confidence: 99%
See 3 more Smart Citations